Development of the Wordwall Game for Learning Mandarin Vocabulary for Grade VI Elementary School - Ani Kariyati; Indrati Kusumaningrum; Fetri Yeni J; Ridwan Ridwan (Postgraduate School, Universitas Negeri Padang, 2021)
Given the circumstances that occur in learning Mandarin, there is still a lack of teacher ability in developing learning media to increase the vocabulary skills of elementary school-age children and teachers are less creative in packaging interesting learning. This study aims to develop word wall media to improve the Chinese vocabulary skills of sixth-grade elementary school children. This research is development research that uses the 4D development model. The research subjects used consisted of 1 material expert, 1 media expert, and 2 linguists. Data collection methods in this study, namely observation, questionnaires, and interviews. The instrument used in this study was a questionnaire or questionnaire. The data analysis technique used is descriptive qualitative and quantitative analysis. The results of the study, namely the assessment by learning material experts got a score of 94% (very good), the results of the learning media expert test got a score of 92% (very good), the results of the language expert test got a score of 96% (very good). Based on the results of the study, it can be concluded that word wall media which was developed to improve the Chinese vocabulary skills of sixth graders of elementary school is suitable for use in the learning process. This research implies that the media developed in the form of word wall media can be used by teachers to improve vocabulary skills in sixth-grade elementary school children.